All-night lingo tango - Hamby, Barbara, 1952- (Pitt poetry series., 2009)
This collection is a love letter to language with poems that are drunk and filled with references to the hyperkinetic world of the twenty-first century. Yet Zeus and Hera tangle with Leda on the interstate; Ava Gardner becomes a Hindu princess; and Shiva, the Destroyer, reigns over all. English is the primary god here, with its huge vocabulary and omnivorous gluttony for new words, yet the mystery of the alphabet is behind everything, a funky puppet masterwho can make a new world out of nothing.